2020
DOI: 10.1088/1361-6382/ab7bff
|View full text |Cite
|
Sign up to set email alerts
|

Generalized off-shell ADT conserved charges in the presence of matter Chern–Simons term

Abstract: In this paper we elevate the formalism for off-shell Abbott-Deser-Tekin (ADT) conserved charges in the presence of arbitrary matter fields to including the internal gauge transformation, when the gauge fields are present. For this purpose, we resort to exact symmetry, and the symmetry generator is combined by diffeomorphism and gauge transformation. For universality, we consider an apparently non-covariant Lagrangian, which contains a matter Chern-Simons term. We show that the elevated off-shell ADT formalism … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…(J. 14) and we directly recover (J.12). This short calculation shows the power of the contracting homotopy operator approach.…”
Section: J1 D-cs Surface Charge From the Contracting Homotopy Operatormentioning
confidence: 73%
See 3 more Smart Citations
“…(J. 14) and we directly recover (J.12). This short calculation shows the power of the contracting homotopy operator approach.…”
Section: J1 D-cs Surface Charge From the Contracting Homotopy Operatormentioning
confidence: 73%
“…In the present notes we extensively explore the first 2 See for instance a recent review about the equivalence among the Iyer-Wald and Barnich-Brandt procedure [13]. Analogously, in [14] was shown that the of-shell Abbot-Deser-Tekin formalism is related to the Iyer-Wald and Barnich-Brandt-Compére formalism. 3 It is worth to note here that the quasi-local treatment for the charge conservation ensures, given a spacetime with exact symmetries, the independence of the radius.…”
Section: Contentsmentioning
confidence: 93%
See 2 more Smart Citations
“…Along another line, general theory of conserved charges based on the cohomology principles was developed by Barnich-Brandt-Compère (BBC) [17][18][19][20]. Recently, an off-shell ADT formalism was proposed by Bouchareb, Clément [21] and Kim-Kulkami-Yi in [22], and subsequently was generalized to including the matter fields [23,24].…”
Section: Introductionmentioning
confidence: 99%